2015
DOI: 10.1007/s10067-015-2930-1
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life assessed by LupusQoL questionnaire and SF-36 in Turkish patients with systemic lupus erythematosus

Abstract: The LupusQoL is a disease-specific health-related quality of life (HRQoL) measure for patients with lupus. We conducted this study to compare the efficiency of LupusQoL-TR (validated Turkish version of the LupusQoL questionnaire) with the 36-item Short-Form Health Survey (SF-36), a generic quality of life (QoL) scale, in Turkish patients with lupus. Both questionnaires were conducted at a single visit to the clinic. Disease activity was measured with the Systemic Lupus Erythematosus Disease Activity Index (SLE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 25 publications
3
23
0
1
Order By: Relevance
“…A multivariate logistic model was built to control for confounding variables. The association of factors with inadequate global HRQoL [26, 27] was determined using odds ratios (ORs) and 95% confidence intervals (95% CIs). All analyses were performed using SPSS version 12.0 (Chicago, IL, USA).…”
Section: Methodsmentioning
confidence: 99%
“…A multivariate logistic model was built to control for confounding variables. The association of factors with inadequate global HRQoL [26, 27] was determined using odds ratios (ORs) and 95% confidence intervals (95% CIs). All analyses were performed using SPSS version 12.0 (Chicago, IL, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Quality of life (QOL) is a multidimensional concept that contains physical, physiological, social heath and individual's satisfaction, and is widely accepted as an important end point in medical care (7,8). The 36-item Short-Form Health Survey (SF-36) questionnaire has been applied widely to assess QOL of people in many areas and studies (9)(10)(11)(12)(13). For example, a study which used SF-36 showed that the health-related quality of life (HRQL) of electric welders was significantly lower than ordinary people (14).…”
Section: Original Articlementioning
confidence: 99%
“…Originally developed in the U.K. [39], the instrument has since been validated in a United States (U.S.) sample of SLE patients [64]. Validity and other psychometric properties of non-English translations of LupusQoL have been published for Spanish [65], Turkish [66, 67], Persian [68], Italian [69], French [70], and Chinese [71] language cohorts. LupusQoL evaluates eight domains including physical health, pain, planning, intimate relationships, burden to others, emotional health, body image, and fatigue.…”
Section: Sle-specific Pro Toolsmentioning
confidence: 99%